2005
DOI: 10.1016/j.cytogfr.2005.04.007
|View full text |Cite
|
Sign up to set email alerts
|

CXC chemokines in angiogenesis

Abstract: CXC chemokines display pleiotropic effects in immunity, regulating angiogenesis, and mediating organ-specific metastases of cancer. In the context of angiogenesis, CXC chemokines are a unique family of cytokines, known for their ability to behave in a disparate manner in the regulation of angiogenesis. Members that contain the 'ELR' motif are potent promoters of angiogenesis, and mediate their angiogenic activity via binding and activating CXCR2 on endothelium. In contrast, members, in general, those are induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
212
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(219 citation statements)
references
References 157 publications
(133 reference statements)
2
212
0
5
Order By: Relevance
“…www.endocrinology-journals.org responsible for the ability of chemokines to attract neutrophils as well as a necessary motif involved in angiogenic properties of these chemokines (Strieter et al 2005). The co-regulation of CXCL1, CXCL3, CXCL5, CXCL6, and CXCL8 in tumors was puzzling.…”
Section: Discussionmentioning
confidence: 99%
“…www.endocrinology-journals.org responsible for the ability of chemokines to attract neutrophils as well as a necessary motif involved in angiogenic properties of these chemokines (Strieter et al 2005). The co-regulation of CXCL1, CXCL3, CXCL5, CXCL6, and CXCL8 in tumors was puzzling.…”
Section: Discussionmentioning
confidence: 99%
“…Neovascularization in fibroproliferative disorders is regulated by an opposing balance between angiogenic and angiostatic factors. Molecules that originally promote angiogenesis include ELR+ CXC chemokines, such as IL-8, whereas ELR– CXC chemokines, such as MIG and IP-10, behave as potent inhibitors of angiogenesis and benefit angiostasis [25]. An imbalance between the expression of pro-angiogenic and angiostatic CXC chemokines, such as an increase in IL-8 and a decrease in IP-10, favoring net angiogenic activity, has been demonstrated in lung fibrosis specimens in IPF [26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Th1 immune responses, it was recently reported that CXCL10 plays a role in maintaining glomerular podocyte function [9, 10]. Moreover, CXCL10 has been demonstrated to be involved in the regulation of mesangial cell proliferation [11, 12], endothelial cell proliferation and angiogenesis and intestinal epithelial cell proliferation [13, 14]. Furthermore, recent work demonstrated that CXCL10 was detected in the urine of transplant recipients [15].…”
Section: Introductionmentioning
confidence: 99%